Refund Psychology - Yu, Tianjiao; Cryder, Cynthia; LeBoeuf, Robyn A (Journal of Consumer Research, 2024)
Abstract Consumers frequently receive refunds from prior purchases. In this research, we examine if money refunded from previous purchases is more likely to be spent than money that does not go through a refund process. Across nine pre-registered studies, we test how consumers’ willingness to spend depends on the transaction history of their money. We find that, when people receive a refund and do not need to replace the originally purchased item, they are more likely to spend the refunded money on a discretionary purchase than they are to spend non-refunded money that is otherwise identical. We suggest that this pattern arises because refunded money is earmarked as “spending money” at the time of the initial purchase and then retains that earmark even after the refund is issued. When refunds arrive, therefore, they seem free from obligations and easy to spend. This research documents the psychology of purchase refunds, a topic largely unaddressed in the mental accounting literature to date.